Regenerative therapy of infrabony defects with or without systemic doxycycline: a randomized placebo-controlled trial - Röllke, Lasse; Kim, Ti-Sun; Kaltschmitt, Jens; Krieger, Jörg; Krigar, Diana-Maria (Journal of clinical periodontology, 2012)
Aim Comparison of regenerative therapy of infrabony defects with and without administration of postsurgical systemic doxycycline (DOXY). Methods In each of 61 patients one infrabony defect was treated with enamel matrix derivative (EMD), EMD plus filler or membrane at two centres. By random assignment patients received either 200 mg DOXY per day or placebo (PLAC) for 7 days after surgery. Prior to and 6 months after surgery probing pocket depths (PPD) and vertical attachment level (PAL-V) were obtained. Results Fifty-four patients (DOXY: 27; PLAC: 27) were re-examined after 6 months and had been treated exclusively with EMD. Seven to 8 days after surgery 81% of defects in both groups showed complete flap closure. In both groups significant (p < 0.001) PPD reduction (DOXY: 3.87 ± 1.44 mm; PLAC: 3.67 ± 1.30 mm) and PAL-V gain (DOXY: 3.11 ± 1.50 mm; PLAC: 3.32 ± 1.83 mm) were observed. However, the differences failed to be statistically significant (PPD: 0.20; p = 0.588; PAL-V: 0.21; p = 0.657). Conclusions Two hundred milligram systemic DOXY administered for 7 days after therapy of infrabony defects with EMD failed to result in better PPD reduction and PAL-V gain compared with PLAC which may be due to low power (50%) and, thus, random chance.
Accepted manuscript online: 01 February 2012
Gesehen am 15.08.2018